Carboxy-methyl-cellulose hydrogel mammary implants: our experience - Valeriani, M; Mezzana, Paolo; Madonna Terracina, F. S (Acta chirurgiae plasticae (English ed.), 2002)
The Authors present their experience with carboxy-methyl-cellulose hydrogel mammary implants. 110 patients have undergone operations since October 1998 with the iimplantion of this type of prosthesis. The results are very good: no major complications, and only 22 patients (20%) showed a II stage capsular contracture and 4 patients (3.6%) a III stage, according to Baker's scale, with an average follow-up of 20 months. The low percentage of capsular contracture and the absence of major complications, let us to conclude that this type of implant is highly tolerated by the human body.
Keywords: Hydrogels; prsní implantáty; pooperační komplikace; mamoplastika; implantace prsní náhrady; sodná sůl karboxymethylcelulosy; Postoperative Complications; ženské pohlaví; lidé; Breast Implantation; Mammaplasty; Carboxymethylcellulose Sodium; Humans; Female; hydrogely; Breast Implants